Joint Consumption Products and Promotion Strategies in Consumers in Spain - Hernández-Zelaya, Sandra Lizzeth (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This paper analyses the consumption of complementary products, which by their nature are consumed or used with others to meet the needs or desires of the consumer. These products can see their link reinforced through price promotions, promotions that exert a lot of influence at the purchase time. To this purpose, a research is carried out with Spanish consumers analysing four categories of food through a survey of consumer behaviour interest. Through the results, it is highlight the importance of identifying complementarity between products, the preference for these complementarities and the planning of promotions between categories to be more effective.